Gonococcal scalp abscess in a neonate delivered by caesarean section. Issue 6 (December 1998) - Varady, E; Nsanze, H; Slattery, T
Abstract : Gonococcal infection in caesarean delivered babies is very rare and is usually limited to ophthalmia neonatorum. The mother had rupture of membranes 14 hours before the caesarean section. The infection was most likely introduced by the fetal scalp electrode probes applied 2 hours before delivery. This is the first reported of a neonatal gonococcal abscess in a caesarean delivered infant.